Behavioural insights teams in practice: nudge missions and methods on trial. (1st January 2021) - Ball, Sarah; Head, Brian W.
Abstract : Behavioural and experimental projects have become increasingly popular with policymakers. Behavioural insights teams have used several policy design and implementation tools drawn from behavioural sciences, especially randomised controlled trials, to test the design of 'nudge' interventions. This approach has attained discursive legitimacy in government agencies seeking to use the best available evidence for behaviourally informed, evidence-based policy innovation. We examine the practices of governmental behavioural insights teams in Australia, drawing on two research projects that included interviews with key personnel. We find that teams make strong commitments to using and promoting randomised controlled trials in government policy innovation. Nevertheless, some members of these teams are beginning to appreciate the constraints of relying solely on randomised controlled trials in the development of behavioural public policy. We conclude that while an initial focus on rigorous trials helped behavioural insights teams establish themselves in policymaking, strict adherence may represent a risk to their long-term growth and relevance.